‘YOU BELIEVE IN GOD’ AND ‘BELIEVE IN GOD’: A CRITICAL STUDY OF JOHN 14:1 - Kuwornu-Adjaottor, Jonathan E. T. (European Scientific Journal, ESJ, 2013)
A study of the grammar of the Greek text of John 14:1 shows that pisteuete appears twice in the verse – on in relation to God and the other in relation to Jesus. Pisteuete has a double meaning; it is an active indicative verb and at the same time an imperative. Both meanings are found in different translations of the text. This study argues that the first pisteuete should be translated as an active indicative verb – “you believe” not as an imperative, “believe”. This is because “you believe” agrees with the context, the situation the disciples were in – troubled. Thus pisteuete eis ton theon kai eis eme pisteuete should be translated, “you believe in God; believe also in me [Jesus]”. This translation is significant because it agrees with the background of the disciples; as Jews they already believe in God before they came to follow Jesus. There is no need to command them to believe in God again in times of trouble. If anything at all they should continue believing in God. Translating the text that way into the Ghanaian languages is of value because, to the Ghanaian/African, belief in God is debatable. Ghanaians believed in God before the Good News about Jesus was brought to them, and they continue to believe in God. As such, any translation of the of the Bible that has to do with belief in God, should take that into consideration.